Cannabinoids: A Guide for Use in the World of Gastrointestinal Disease. Issue 9 (October 2020) - Unal, Ece; Anderson, Brigitte; Helber, Andrew; Marks, John H.
Abstract : Cannabinoids have been known as the primary component of cannabis for decades, but the characterization of the endocannabinoid system (ECS) in the 1990s opened the doors for cannabis' use in modern medicine. The 2 main receptors of this system, cannabinoid receptors 1 and 2, are found on cells of various tissues, with significant expression in the gastrointestinal (GI) tract. The characterization of the ECS also heralded the understanding of endocannabinoids, naturally occurring compounds synthesized in the human body. Via secondary signaling pathways acting on vagal nerves, nociceptors, and immune cells, cannabinoids have been shown to have both palliative and detrimental effects on the pathophysiology of GI disorders. Although research on the effects of both endogenous and exogenous cannabinoids has been slow due to the complicated legal history of cannabis, discoveries of cannabinoids' treatment potential have been found in various fields of medicine, including the GI world. Medical cannabis has since been offered as a treatment for a myriad of conditions and malignancies, including cancer, human immunodeficiency virus/acquired immunodeficiency syndrome, multiple sclerosis, chronic pain, nausea, posttraumatic stress disorder, amyotrophic lateral sclerosis, cachexia, glaucoma, and epilepsy. This article hopes to create an overview of current research on cannabinoids and the ECS, detail the potential advantages and pitfalls of their use in GI diseases, and explore possible future developments in this field.